2014
DOI: 10.1208/s12249-014-0167-y
|View full text |Cite
|
Sign up to set email alerts
|

Glass Delamination: a Comparison of the Inner Surface Performance of Vials and Pre-filled Syringes

Abstract: The occurrence of glass delamination is a serious concern for parenteral drug products. Over the past several years, there has been a series of product recalls involving glass delamination in parenteral drugs stored in vials which has led to heightened industry and regulatory scrutiny. In this study, a two-pronged approach was employed to assess the inner surface durability of vials and pre-filled syringes. Non-siliconized syringes were used in order to directly compare glass to glass performance between vials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 24 publications
0
16
0
7
Order By: Relevance
“…Delamination within glass vials is affected by both the glass manufacturing process and the chemical characteristics of the drug, particularly if acidic or caustic. 26,27 The glass lamellae subsequently found in 1.9% of stored vials in lot 2 of the trial drug raised the question whether the observed harmful effect of myo-inositol could have been due to these particles. However, detailed analyses revealed that there were no differences in the outcomes for infants treated with myo-inositol between the 2 lots of the trial drug.…”
Section: Discussionmentioning
confidence: 99%
“…Delamination within glass vials is affected by both the glass manufacturing process and the chemical characteristics of the drug, particularly if acidic or caustic. 26,27 The glass lamellae subsequently found in 1.9% of stored vials in lot 2 of the trial drug raised the question whether the observed harmful effect of myo-inositol could have been due to these particles. However, detailed analyses revealed that there were no differences in the outcomes for infants treated with myo-inositol between the 2 lots of the trial drug.…”
Section: Discussionmentioning
confidence: 99%
“…However, glass presents inherent risks such as breakage and delamination, which may occur during the manufacturing processes, shipping, and/or storage. 2 In addition, lubricants such as silicone oil are commonly used to insure smooth operation of the plunger within the syringe barrel. The presence of silicone oil can lead to undesirable protein aggregation and particle formation in syringes, which in turn may cause adverse immune responses in patients.…”
Section: Introductionmentioning
confidence: 99%
“…The main component of a PFS is the barrel, which is traditionally made of glass. Recently, PFSs composed of plastic (polymer) barrels (P‐PFS) have been explored and applied practically to mitigate the problems associated with glass (e.g., shock resistance, delamination, silicone oil, and elution of tungsten oxide). Cyclic olefin polymers (COPs), cyclic olefin copolymers, and polypropylene have been used for this purpose .…”
Section: Introductionmentioning
confidence: 99%